Proposed Business Continuity Plan Information Technology using ISO 22301 And ISO 27031 - Ari Cahaya Puspitaningrum (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Majority of organizations have a high dependence on the role of information technology (IT). IT has a very important role for a business, so IT implementation needs to be protected from various threats and disruptions to avoiding IT failures and the occurrence of IT risks that will poor impact to business activities of the organization. To ensure the sustainability of the business, an organization needs to have a business continuity planning (BCP) document. BCP is a complete set of procedures to respond to the disruption of business operations effectively and efficiently, so that business can continue continuously. During all this time, not many organizations have awareness to the importance of good BCP implementation. It is caused by the lack knowledge how to design BCP document with comprehensive, included business impact analysis and prioritize critical business processes. Organizations without BCP implementation, would potentially loss profit, because they did not have any preparation in case of disaster related to information technology which has crusial role in business organizations. This indicated that BCP is important to be implemented throughout the organization for business to continue continuously as it reduces the negative impact of business interruptions. The output of this research is the proposed BCP in the oil and gas industry using ISO 22301:2012, ISO 27031:2011 references related to business continuity in information technology, and previous research on BCP elements.